Association between social capital and sleep duration among rural older adults in China - Le Yang; Hongman Wang; Jingmin Cheng (BMC, 2022)
Abstract Objective Sleep disturbances are great challenges to older adults' health promotion. The study tested gender differences in the association between different dimensions of social capital and self-reported sleep duration of Chinese rural older adults. Design The data of rural older adults were extracted from a national cross-sectional survey of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) and analyzed in this study. Setting CLHLS covered 23 provinces in China. Participants The 6552 rural respondents aged ≥65 years old were involved. Main outcome measures Generalized trust, informal social participation, formal social participation and social support were used to assess social capital. Self-reported sleep duration was measured as health outcome. Results Low level of generalized trust had harmful effect on insufficient sleep (AOR 1.110, 95% CI 1.018-1.324), and having no formal or informal social participation was significantly positively associated with long sleep (AORformal 1.424, 95% CI 1.007-2.013; AORinformal 1.241, 95% CI 1.016-1.516). Rural older female adults with no emotional social support had higher odds of insufficient sleep (AOR 1.502, 95% CI 1.258-1.978). Meanwhile, both informal and formal social participation showed inverse association with long sleep for females. Conclusions This study found the relationship between social capital, sleep duration and the gender differences in Chinese rural older adults. More targeted sleep disturbance interventions could be taken in social capital of rural older adults, and gender differences should be considered when making social capital-embedded health promotion policies and interventions.